2020
DOI: 10.1002/advs.202000917
|View full text |Cite
|
Sign up to set email alerts
|

Hexagonal BN‐Assisted Epitaxy of Strain Released GaN Films for True Green Light‐Emitting Diodes

Abstract: Epitaxial growth of III‐nitrides on 2D materials enables the realization of flexible optoelectronic devices for next‐generation wearable applications. Unfortunately, it is difficult to obtain high‐quality III‐nitride epilayers on 2D materials such as hexagonal BN (h‐BN) due to different atom hybridizations. Here, the epitaxy of single‐crystalline GaN films on the chemically activated h‐BN/Al 2 O 3 substrates is reported, paying attention to interface atomic configu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 52 publications
1
30
0
Order By: Relevance
“…As reported by Trindade et al 34 , the temperature increase due to the increase of current injection should lead to a red shift whereas the reduced quantum confined stark effect (QCSE) while increasing the current injection should lead to a blue shift. In the case of these VTF-LEDs on copper, the absence of a red shift could be attributed to the high thermal dissipation capability of the copper substrate, whereas the absence of a blue shift could be attributed to the relaxation of residual compressive strain in the GaN-based films grown on h-BN, that diminishes the QCSE in the quantum wells as reported by Liu, F et al 31 . Finally, Figure 3e shows both the I-V characteristic and a photograph of a large size (4 mm x 4 mm) VTF-LED operated at a current of 500 mA.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…As reported by Trindade et al 34 , the temperature increase due to the increase of current injection should lead to a red shift whereas the reduced quantum confined stark effect (QCSE) while increasing the current injection should lead to a blue shift. In the case of these VTF-LEDs on copper, the absence of a red shift could be attributed to the high thermal dissipation capability of the copper substrate, whereas the absence of a blue shift could be attributed to the relaxation of residual compressive strain in the GaN-based films grown on h-BN, that diminishes the QCSE in the quantum wells as reported by Liu, F et al 31 . Finally, Figure 3e shows both the I-V characteristic and a photograph of a large size (4 mm x 4 mm) VTF-LED operated at a current of 500 mA.…”
Section: Resultssupporting
confidence: 53%
“…The third point is that using 2D crystal with no free dangling bonds on the surface gives rise to a new mechanism of growth called van der Waals (vdWs) epitaxy. With vdWs epitaxy the GaN buffer layer has less residual stress because it is weakly bonded to the 2D layer 31 . In addition, a low temperature epigrowth to move from 3D to 2D GaN buffer layer is not needed, and a 0.5-𝜇𝑚-thick buffer layer instead of 3-4 𝜇𝑚 for standard epitaxy on sapphire is sufficient.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been found that h-BN layers on Al 2 O 3 acts as an ideal substrate to nucleate III-N epitaxial films for photonics applications. Liu Fang ( Liu et al., 2020 ) and coworkers first synthesized crystalline h-BN films on large-area Al 2 O 3 (0001) substrates using plasma-assisted MBE (PA-MBE) at 900°C at a growth rate of 0.2 nm/min. The PA-MBE growth of the h-BN layer was followed by the high temperature annealing to improve the h-BN crystallinity.…”
Section: Metal-free Direct Growth Of Hexagonal Boron Nitridementioning
confidence: 99%
“…Since the dislocation density is significantly reduced for the MGaN, the efficient stress release could be attributed to the remission of thermal/ lattice mismatch between the GaN epilayer and sapphire substrate by the MoS 2 insert layer, which is consistent with the previous works about the van der Waals epitaxy of III-nitrides with graphene as the buffer layer. [12][13][14][15] Besides, the FWHM of MGaN E 2 (High) mode is broad compared to that of the SGaN, proving the unintentional impurities incorporation and enhanced phonondefect scattering, which is in accordance with the missing of A 1 (LO) mode in the MGaN.…”
Section: The Van Der Waals Epitaxy Of High-quality Gan Epilayers With Released Stressmentioning
confidence: 68%
“…Recently, the high-quality and stress-free III-nitrides epitaxy on 2D layers (including h-BN and graphene) are developed, which is socalled as van der Waals epitaxy. [13][14][15] This innovation relies on the excellent stability and weak van der Waals interlayer interaction of 2D insert layers, which fundamentally solves the trouble induced by the heteroepitaxy. As the trade-off, the atomic flatness surface and scarce dangling bonds of h-BN and graphene have made difficulties in III-nitride nucleation.…”
mentioning
confidence: 99%